(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The article examines the role of national and universal values in the development of interethnic relations in the new Uzbekistan. Strengthening interethnic, interethnic and interfaith cooperation and solidarity in the world largely depends on the effective implementation of tolerance in the life of society - one of the universal principles of national ideology.